High performance visualization of human tumour growth software - Norma Alias; Norfarizan Mohd. Said, author; Siti Nur Hidayah Khalid, author; Dolly Sin Tien Ching, author; Phang Tau Ing, author; International Meeting High Performence Computing for Computational Sciences (8th : 2008 : Toulouse, France) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL